On gestating and giving birth to a child with congenital zika virus syndrome: a case study - Alves, Maria José Cremilda Ferreira; Melo, Ana Paula Lopes de; Valongueiro, Sandra; Santos, Mariana Olívia Santana dos (Saúde e Sociedade, 2022)
This study analyzes the context of pregnancy, prenatal care and birth of children with Congenital Zika Syndrome (CZS). A single case exploratory study was conducted with a mother of a child diagnosed with CZS in Pernambuco, Brazil. Data were collected by an in-depth interview and content was categorized into four themes: discovery of pregnancy; conditions of prenatal and childbirth care; conditions of diagnosis and childcare; and feelings involved in the pregnancy discovery and syndrome diagnosis. This case study highlights failures in reproductive planning and in prenatal and childbirth care; unpreparedness of health professionals; and significant changes in the family’s routine, which imply difficult choices under a deficient public health care. CZS epidemic uncovered problems that go beyond mosquito vector control. The current scenario highlights the vulnerabilities of these families, intensified by the emergence and consequences of COVID-19, which has further exposed the weaknesses of women’s comprehensive health care and the need to maintain an articulated and resolute network in health care and surveillance.